Does financial flexibility enhance firm value? A comparative study between developed and emerging countries - Seda Bilyay-Erdogan (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
This paper investigates the effect of financial flexibility on firm value, on a comparative basis between developed and emerging countries in Europe. Our dataset covers 4,334 companies from 15 developed and 1,436 companies from 6 emerging countries in Europe for the period between 2000 and 2016. First, depending on companies' maintenance of leverage that is below-predicted levels for a successive number of years, I identify the financially flexible companies in the sample. Second, I examine whether financial flexibility affects firm value. Our results demonstrate that firms' financial flexibility positively contributes to firm value in all estimations. Furthermore, this study presents unprecedented evidence that the effect of financial flexibility on firm value is more significant for emerging countries when compared to developed countries in Europe. Moreover, I demonstrate for the first time that firm characteristics, including firm size and age, which proxy for asymmetric information within a company, negatively moderate the relationship between flexibility and firm value. Managers, both in developed and in emerging countries, who aim to surge their firm value up, should give importance to the maintenance of financial flexibility in their capital structure decisions. Last, managers of relatively smaller and younger companies should put more emphasis on becoming financially flexible if they want to improve their firms' value.
Keywords: G03; G30; G32; 650; financial flexibility; firm value; leverage; emerging and developed countries; GMM